2017
DOI: 10.12816/0042589
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge and Attitude and Practice of Parents about Immunization in Jeddah City, 2017

Abstract: Background: Immunization has shown a major preventive aspects of infectious diseases, disability and death. Objectives: Assessing the Knowledge, attitude and practice (KAP) of Saudi parents in Jeddah City regarding the immunization programs for children, Saudi Arabia (KSA), 2017. Methods: It is a cross sectional survey study that was carried among 600 different Saudi parents form different parts of Jeddah City for 3 months from May to July 2017. The parents completed a questionnaire that contains 4 different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 2 publications
7
7
1
Order By: Relevance
“…Hence there is a likelihood of them receiving more accurate information. The level of knowledge found in this study was however lower than what was found by Alenazi et al (2017) in Egypt, Joseph, Devarashetty, Reddy, and Sushma (2015) in Bengaluru in India and Oryema et. al (2017) in Uganda.…”
Section: Knowledge Attitude and Practices Of Mothers/caregivers Towcontrasting
confidence: 85%
See 1 more Smart Citation
“…Hence there is a likelihood of them receiving more accurate information. The level of knowledge found in this study was however lower than what was found by Alenazi et al (2017) in Egypt, Joseph, Devarashetty, Reddy, and Sushma (2015) in Bengaluru in India and Oryema et. al (2017) in Uganda.…”
Section: Knowledge Attitude and Practices Of Mothers/caregivers Towcontrasting
confidence: 85%
“…This practice could be due to the counseling given mothers/caregivers during immunization on how to manage any adverse reaction to immunization. This confirms what was found by Alenazi et al (2017) in their study in Italy who recorded that 85.2% managed swelling by cold compress, and 87.2% used analgesics for swelling and pain after vaccination (Alenazi et al, 2017). However, a survey conducted in Uganda argued that fear of side effects, ignorance, laziness, of mothers/caregivers contribute to low immunization patronage (Vonasek et al, 2016).…”
Section: Knowledge Attitude and Practices Of Mothers/caregivers Towsupporting
confidence: 76%
“…Several studies have been conducted to analyze the knowledge and attitude of postnatal mothers toward childhood vaccination. [25][26][27][28] The present study aims to realize the knowledge and attitude of Malaysian postnatal mothers for different sociodemographic status toward the childhood immunization. The internal consistency reliability of the final questionnaire was good for both knowledge and attitude.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a descriptive prospective study conducted on (140) nursing mothers at a child hospital in south-west Nigeria was reported that the majority of study sample (71.4%) has adequate knowledge. On the other hand, another study in Jeddah City was indicated that most of the participants (87.2%) had a high level of knowledge about the preventive measures and the benefit of vaccination for children [14], [15] . The findings of this study indicated that no significant association was found between parents' knowledge and their some socio-demographical characteristics.…”
Section: Overall Assessment Of Parents' Knowledge Towards Immunizationmentioning
confidence: 99%